Song of Solomon - Morrison, Toni (Vintage International, Vintage Books, a division of Random House LLC, 2004)
Milkman Dead was born shortly after a neighborhood eccentric hurled himself off a rooftop in a vain attempt at flight. For the rest of his life he, too, will be trying to fly. With this brilliantly imagined novel, Toni Morrison transfigures the coming-of-age story as audaciously as Saul Bellow or Gabriel García Márquez. As she follows Milkman from his rustbelt city to the place of his family's origins, Morrison introduces an entire cast of strivers and seeresses, liars and assassins, the inhabitants of a fully realized black world.